Studies on the Mass Nesting (Arribada) of Pacific Ridley Turtles, Lepidochelys olivacea in Bhitarkanika Wildlife Sanctuary, Orissa, India - Kar, Sudhakar (Indian Forester, 1993)
Gahirmatha beach in Bhitarkanika Wildlife Sanctuary is known to be the largest Sea turtle rookery in the whole world. Minimum 2.0 lakh to maximum 6.5 lakh sea turtles visit the beach annually for nesting and egg laying. Studies on ecology and biology of sea turtles have been taken up since over a decade and this paper gives an overview of the 'arribada' in Orissa coast.